2017
DOI: 10.1007/s11356-017-0463-7
|View full text |Cite
|
Sign up to set email alerts
|

Automotive brake wear: a review

Abstract: Road transport systems generate toxic particulate matter (PM) when in motion, that ultimately finds its way to the atmosphere. The PM produced by road transport systems can be broadly classified as exhaust and non-exhaust emissions. Exhaust emission is primarily due to product of combustion, as is the case of internal combustion engines and the PM is released to the atmosphere through the tail. Non-exhaust PM sources can be classified as sources such as emissions due to brake wear, tyre wear, road surface wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…However, in many latest studies, Cu has been identified as traffic pollution; for this reason, Cu was included in our research. Copper emission is being caused by wearing of brake pads in road vehicles (Straffelini et al 2015;Wahid 2018). The chosen roads and two exits to Jędrzejów town have all grade-separated junctions.…”
Section: Resultsmentioning
confidence: 99%
“…However, in many latest studies, Cu has been identified as traffic pollution; for this reason, Cu was included in our research. Copper emission is being caused by wearing of brake pads in road vehicles (Straffelini et al 2015;Wahid 2018). The chosen roads and two exits to Jędrzejów town have all grade-separated junctions.…”
Section: Resultsmentioning
confidence: 99%
“…The used ecoinvent processes "treatment of tire wear emissions", "treatment of road wear emissions" and "treatment of brake wear emissions" were created for a passenger car. Since the weight is the crucial factor for these types of emissions given the same driving and material characteristics, the original data is changed to the e-moped weight plus the weight of an average person in Germany [52][53][54]. Regarding the fleet's battery charging, the German power grid mix of the year 2019 is used.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…The size of PMs produced by brake wear may be airborne due to local turbulence etc. The release of these toxic particles into the environment may differ in large cities, especially during rush hours when braking is high, due to the frequency of stopping and starting of a large number of vehicles and turbulence of the air (Wahid, 2018).…”
Section: Introductionmentioning
confidence: 99%